Correlation of Anthropometric Measurements with Hamstring Graft Size in Anterior Cruciate Ligament Reconstruction in Nepalese Population: A Prospective Observational Study - Nepal, Santosh; Gupta, Mithilesh Kumar; Panthee, Rajan; Kafle, Gokul; Sah, Raj Kumar (Journal of Karnali Academy of Health Sciences, 2023)
Background: The use of autologous hamstring tendon for arthroscopic Anterior Cruciate ligament (ACL) reconstruction is very common. The size of hamstring tendons varies significantly between individuals, and graft diameter is unpredictable. Anthropometric measurements may be a simple way to estimate hamstring tendon length and diameter. This study aims to determine the correlation between anthropometric measurements of patients with length and diameter of harvested hamstring autograft during ACL reconstruction.Methods: A prospective observational study was carried out after ethical approval. All patients who underwent arthroscopic ACL reconstruction from 1 March 2022 to 30 April 2023 in Birat Medical College Teaching Hospital were included. Fourty seven patients’ age, sex, height, weight and thigh length were recorded preoperatively. Hamstring tendons were harvested and length of the semitendinosus tendon and diameter of the quadrupled graft (doubled semitendinosus and doubled gracilis) was measured intraoperatively. We used Pearson’s correlation coefficient to observe the relationship between anthropometric measurements and graft variables.Results: Mean length of harvested semitendinosus tendon was 27.4 ± 1.8 cm and mean quadrupled hamstring autograft diameter was 7.4 ± 0.8 mm. A significant positive correlation between graft variables (semitendinosus tendon length and quadrupled hamstring autograft diameter) and patients’ height and thigh length was found. Regression equations for predicting Semitendinosus tendon length and quadrupled hamstring autograft diameter from thigh length in males and females are also derived.Conclusion: Height and thigh length of patients are useful parameters for predicting semitendinosus tendon length and quadrupled hamstring graft diameter before ACL reconstruction